Gut microbiota disorders in obesity and colorectal cancer - Szponarowicz, Patrycja; Rzeszutko, Mateusz; Snopkowski, Bartosz; Raczkiewicz, Przemysław; Panek, Eliasz; Jasłowski, Damian; Panasiuk, Dominika; Korzec, Tomasz; Sosnowski, Jakub; Skrętowicz, Mateusz (Journal of Education, Health and Sport, 2023)
Obesity and related diseases such as colorectal cancer are an important clinical problem in highly developed countries. In this article, the relationship between the occurrence of these diseases and the gut microbiome is presented on the basis of scientific research. The gut microbiome increases the energy value of consumed meals by breaking down to simpler substances not digested by human enzymes, and is involved in the regulation of lipid and glucose metabolism in the body. A proper microbiota influences the formation of SCFAs, or short-chain fatty acids, which have a protective effect on intestinal cells. Intestinal dysbiosis affects endotoxaemia and inflammation, which accompanies cancer and obesity.